2015
DOI: 10.1002/joc.4422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating changes in season length, onset, and end dates across the United States (1948–2012)

Abstract: Discussed in a global context, the issue of scale is important to consider as it relates to climate change. As climatological studies utilize temporally and spatially static definitions of seasonal definitions, the understanding of seasonal change may be limited by the way in which seasons are defined. This research serves as a challenge to this perspective by examining the changes in seasons by incorporating variability into the way in which seasons are defined. Temporally and spatially variable seasons were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 29 publications
4
43
0
Order By: Relevance
“…These changes are more noticeable in Central and Southern Chile for those rain gauges located around 40 ∘ S, which showed mostly significant negative (positive) trends during austral autumn (winter) (Figure 8(f) and (g)). Seasonal changes have recently been reported for United States by Allen and Sheridan (2015), who analysed temperature data concluding that late starts of autumn and winter have been observed while earlier onsets of spring and summer have taken place between 1948 and 2012.…”
Section: Seasonal Ratio Indexmentioning
confidence: 99%
“…These changes are more noticeable in Central and Southern Chile for those rain gauges located around 40 ∘ S, which showed mostly significant negative (positive) trends during austral autumn (winter) (Figure 8(f) and (g)). Seasonal changes have recently been reported for United States by Allen and Sheridan (2015), who analysed temperature data concluding that late starts of autumn and winter have been observed while earlier onsets of spring and summer have taken place between 1948 and 2012.…”
Section: Seasonal Ratio Indexmentioning
confidence: 99%
“…Global warming caused by increasing emissions of greenhouse gases is a major concern around the world (Allen et al 2010;Vörösmarty et al 2000). The mean ambient air temperature of the Earth rose by approximately 0.85°C from 1880 to 2012 (Allen and Sheridan 2016;Hartmann et al 2013). This is reported to have caused climate change (Richardson et al 2018), with increasing frequency of droughts, floods, and extreme weather events in many parts…”
Section: Introductionmentioning
confidence: 99%
“…The overall shortening of winter that we observed was largely due to an earlier spring onset; 22 of 37 sites exhibited significantly earlier loss of continuous cold conditions as compared with only 6 of 37 sites where the onset of cold conditions occurred later. Other studies have likewise reported that earlier springs drove trends in reduced winter duration (Dye 2002, Allen and Sheridan 2016, Kutta and Hubbart 2016. In addition, proxies for the beginning of spring, particularly phenological data describing budbreak, leaf emergence, and leaf out, have been widely used to document earlier springs (Richardson et al 2006, Schwartz et al 2013, Piao et al 2015, providing further evidence for an advancement of spring onset by −0.8 to −0.9 d per decade in the northeastern US from 1901 to 2012 (Monahan et al 2016).…”
Section: Discussionmentioning
confidence: 99%